Managing Elevated Risk Global Liquidity, Capital Flows, and Macroprudential Policy$1 (BAn Asian Perspective /s - Azis, Iwan J.; Shin, Hyun Song.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book discusses the risks and opportunities that arise in Emerging Asia given the context of a new environment in global liquidity and capital flows. It elaborates on the need to ensure financial and overall economic stability in the region through improved financial regulation and other policy measures to minimize the emergent risks. "Managing Elevated Risk: Global Liquidity, Capital Flows, and Macroprudential Policy$1 (BAn Asian Perspective" also explores the range of policy options that may be deployed to address the impact of global liquidity on domestic financial and socio-economic conditions including income inequality. The book is primarily aimed at policy makers, financial market regulators and supervisory agencies to help them improve national regulatory systems and to promote harmonization of national regulations and practices in line with global standards. Scholars and researchers will also gain important information and knowledge about the overall impacts of changing global liquidity from the book.s
Contents -- Foreword -- Chapter 1: Introduction and Overview -- Chapter 2: The Three Phases of Global Liquidity -- 2.1: Conceptual and Measurement Issues -- 2.2: First Phase of Global Liquidity -- 2.2.1: Round-trip Bank Flows to the US -- 2.2.2: Banking Sector Flows to the Rest of the World -- 2.2.3: Exchange Rates and Leverage -- 2.3: Second Phase of Global Liquidity -- 2.4: The Case of Emerging Asia -- 2.5: Third Phase and Onward -- 2.6: References -- Chapter 3: Early Warning Indicators for Financial Vulnerabilities -- 3.1: Principles for Selection of Early Warning Indicators -- 3.2: Core and Noncore Liabilities -- 3.3: References -- Chapter 4: Emerging Asia$1 (Bs Noncore Liabilities and Policy Effectiveness -- 4.1: Bank-led Flows, Noncore Liabilities, and Credit Growth -- 4.2: Reassessing Monetary Policy -- 4.3: Appendix -- 4.4: References -- Chapter 5: Capital Flows and Income Distribution -- 5.1: National Policy Remains Key -- 5.2: How Capital Flows Affect Income Inequality -- 5.3: Prioritization for a Multi-Objective Goal -- 5.4: Appendix -- 5.5: References -- Chapter 6: Policy Implications -- 6.1 Tailoring Policies to Vulnerabilities -- 6.2 Macroprudential Tools -- 6.2.1 Bank Capital-Oriented Tools -- 6.2.1.1 Capital Requirements that Adjust Over the Cycle -- 6.2.1.2 Forward-Looking Provisioning -- 6.2.1.3: Leverage caps -- 6.2.1.4: Loan-To-Value and Debt-Service-To-Income Caps -- 6.2.1.5: Loan-to-Deposit caps -- 6.2.1.6: Levy on Noncore Liabilities -- 6.2.1.7: Unremunerated Reserve Requirements -- 6.2.2: Relative Merits of URR versus Levies/Taxes -- 6.2.3: Relationship with other Stabilization Policies -- 6.3: Financial Integration and Institutional Design -- 6.4: Policy Choices -- 6.5: References.s
Keywords: Economics; Development Economics; Economic policy; Economics/Management Science; Finance/Investment/Banking.; Economic Policy; Development Economics